My passion for design - Streisand, Barbra (New York : London : Viking, 2010)
An illustrated tour of Streisand's homes and collections. The book contains photographs of the rooms she has decorated, the furniture and art she has collected, and the gardens she has planted.
An elegant barn -- The mill house -- The barn... a view inside -- Grandma's house -- The main house.
Keywords: Streisand, Barbra -- Homes and haunts -- California -- Malibu; Architecture, Domestic -- California -- Malibu; Dwellings -- California -- Malibu -- Design and construction; Interior decoration -- California -- Malibu